Pengaruh Persepsi Kemudahan dan Kepercayaan Terhadap Minat Penggunaan Layanan Transportasi Online Grab di Kota Bekasi - Nadariansyah, Raihan; Prihadini, Diana (JAMBIS : Jurnal Administrasi Bisnis, 2024)
The objective of this research was to determine the Effect of Convenience and Trust Perception towards the Interest of Use of Grab Online Transportation Services in Bekasi City. This research used quantitative approach method. Besides, the type of this research was descriptive method. The population used in this research was all users of Grab online transportation services in Bekasi City. The data collection technique used questionnaires and observations. The sampling technique used Hair’s opinion with the total sample of 150 respondents. The data analysis was a multiple linear regression system using the Iunan tool with the assistance of IBM Statistics version 25.0. The results of this research showed that there was a significant effect between the convenience perception variable towards the interest of use for about 83.1%, there was a significant positive effect between the trust perception variable towards the interest of use for about 86.4%, there was a simultaneous positive and significant effect between the convenience and trust perception variable towards the interest of use for about 81.1%, then the rest of 18.9% was explained by other variables that were not examined in this research.